2018
DOI: 10.1111/pcn.12645
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation analyses of the candidate genes identified by a methylome‐wide association study revealed common epigenetic alterations in schizophrenia and bipolar disorder

Abstract: Hypomethylation of FAM63B and IR on chromosome 16 could be common epigenetic risk factors for SZ and BD. Further comprehensive epigenetic studies for BD, such as MWAS, will uncover the extent of similarity and uniqueness of epigenetic alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…DNA methylation can be either assessed over the entire genome (whole‐genome methylation profiling) as explained in an overview by Rakyan et al or by candidate studies designed to search specifically for DMRs or CpGs in specific genes or regions in the DNA . Three techniques are currently available for detection of methylation status at DMRs or CpGs: bisulphite sequencing, microarrays or bead chips and methyl‐sensitive cut counting (MSCC) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation can be either assessed over the entire genome (whole‐genome methylation profiling) as explained in an overview by Rakyan et al or by candidate studies designed to search specifically for DMRs or CpGs in specific genes or regions in the DNA . Three techniques are currently available for detection of methylation status at DMRs or CpGs: bisulphite sequencing, microarrays or bead chips and methyl‐sensitive cut counting (MSCC) …”
Section: Introductionmentioning
confidence: 99%
“…14 DNA methylation can be either assessed over the entire genome (whole-genome methylation profiling) as explained in an overview by Rakyan et al 17 or by candidate studies designed to search specifically for DMRs or CpGs in specific genes or regions in the DNA. 18 Three techniques are currently available for detection of methylation status at DMRs or CpGs: bisulphite sequencing, microarrays or bead chips and methyl-sensitive cut counting (MSCC). 19 Bisulphite sequencing exploits the current inability of DNA sequencing techniques to differentiate between methylcytosine and cytosine due to similar base pairing characteristics between both molecules.…”
mentioning
confidence: 99%
“…FAM63B (Mindy‐2) is a deubiquitinating enzyme found in the cerebellum and in the pineal body . Epigenetic alterations to FAM63B have been associated with schizophrenia and bipolar disorder …”
Section: Discussionmentioning
confidence: 99%
“…48 Epigenetic alterations to FAM63B have been associated with schizophrenia and bipolar disorder. 49,50 Methodological differences between the two autoantibody assays must be considered as explanations to why the herein identified candidate antigens could not be verified, including differences in protein folding, post-translational modification and immobilization of the antigen. These aspects are also relevant to a broader discussion on the difficulties in confirming suggested candidate autoantigens in NT1.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation involves the addition of a methylgroup to the carbon-5 position of a cytosine residue (Razin and Cedar, 1991): this may be associated with increased or decreased gene expression depending on the genomic region in which it occurs (Jones, 2012;Watkeys et al, 2018). Both candidate-and genome-wide studies have revealed differential methylation of various sites in SZ (Hannon et al, 2016;Montano et al, 2016;Ruzicka et al, 2015;Yoshino et al, 2016), with some studies suggesting overlapping patterns of DNA methylation in BD (Dempster et al, 2011;Sugawara Poly-methylomic Profile Scores for schizophrenia et al, 2018), although there have been few replications at individual CpG sites (Pries et al, 2017;Teroganova et al, 2016).…”
Section: Introductionmentioning
confidence: 99%